2014 IPA membership by country. (30th March 2015) - Keating, Patricia A.
Abstract : The following is a list of the countries of the current membership of the Association, based on the Association's records in November 2014. The numbers in parentheses indicate the total number of members per country (Life, Full, and Student combined). There are a total of 370 members from 49 countries. Individual members' names are no longer published.